2007
DOI: 10.1182/blood-2006-04-016535
|View full text |Cite
|
Sign up to set email alerts
|

Functional conservation of erythropoietin signaling in zebrafish

Abstract: Erythropoietin (Epo) and its cognate receptor (EpoR) are required for maintaining adequate levels of circulating erythrocytes during embryogenesis and adulthood. Here, we report the functional characterization of the zebrafish epo and epor genes. The expression of epo and epor was evaluated by quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) and whole-mount in situ hybridization, revealing marked parallels between zebrafish and mammalian gene expression patterns. Examination of the hypochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 64 publications
(71 reference statements)
9
109
0
Order By: Relevance
“…We further have discovered that a major source of Epo for primitive erythropoiesis might be a subpopulation of neural and neural crest cells, which we refer to as NEP cells. Consistent with our observation, the principal Epo-producing tissue in zebrafish larvae is neural tissue, and Epo production moves to the heart and liver during adulthood 40,41 . We also observed that a subpopulation of NEP cells migrate along the blood vessels in the intersomitic space.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We further have discovered that a major source of Epo for primitive erythropoiesis might be a subpopulation of neural and neural crest cells, which we refer to as NEP cells. Consistent with our observation, the principal Epo-producing tissue in zebrafish larvae is neural tissue, and Epo production moves to the heart and liver during adulthood 40,41 . We also observed that a subpopulation of NEP cells migrate along the blood vessels in the intersomitic space.…”
Section: Discussionsupporting
confidence: 77%
“…We have also observed that Epo-KO embryos exhibit no apparent abnormality until E11.5 in non-haematopoietic organs. In zebrafish, the overexpression and knockdown of Epo dramatically alter erythropoiesis in the embryonic intermediate cell mass and the adult kidney, but these alterations in Epo levels do not affect the development of non-haematopoietic systems 41 . Moreover, NEP cells express low EpoR mRNA levels compared with haematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that NEP-derived cells in organs other than the kidney and liver may retain their ability to produce Epo under pathological conditions. Interestingly, in Zebrafish, one of the major Epo-producing sites is the brain (Paffett-Lugassy et al 2007). Therefore, transient Epo production by NEP cells in mouse embryos may support the so-called "recapitulation theory", which argues that ontogeny recapitulates phylogeny (Sander 2002).…”
Section: Neural Epo-producing (Nep) Cellsmentioning
confidence: 99%
“…At the transcriptional level, Epo gene expression is tightly regulated by hypoxia-inducible factors (HIFs), which are the master transcription factors for oxygen-dependent gene regulation (Suzuki et al 2007;Miyata et al 2013;Franke et al 2013). Because non-mammalian Epo genes also respond to hypoxic stimuli (Paffett-Lugassy et al 2007), Epo is considered to be evolutionarily indispensable for maintaining oxygen homeostasis in animals with hemoglobins encapsulated by erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation